Copy number variation detection using SNP genotyping arrays in three Chinese pig breeds. (15th January 2015) - Dong, K.; Pu, Y.; Yao, N.; Shu, G.; Liu, X.; He, X.; Zhao, Q.; Guan, W.; Ma, Y.
Summary We performed genome‐wide CNV detection based on SNP genotyping data of 96 Chinese‐native Tibetan, Dahe and Wuzhishan pigs. These pigs are particularly interesting because of their excellent adaptation to hypoxia or small body size, which facilitates the use of them as models of different human diseases in addition to valuable agricultural animals. A total of 105 CNV regions (CNVRs) were identified, encompassing 16.71 Mb of the pig genome. Seven of 10 (70%) CNVRs selected randomly were validated by quantitative real‐time PCR. Comparison with previous studies revealed 25 (23.81%) novel CNVRs, indicating that CNV coverage of the pig genome is still incomplete and there exists large diversity between pig breeds. Functional analysis of genes located in these CNVRs confirmed the high representation of genes involved in sensory perception, neurological system processes and other basic metabolic processes. In addition, the majority of these CNVRs were detected to span reported pig QTL that affect various traits, which highlighted three biologically interesting genes with copy number changes (i.e., ANKRD34B, FAM110B and ABCG1). These genes may have economic importance in pig breeding and are worth being further investigated. We also obtained some CNVRs harboring genes that had human orthologs involved in human diseases such as cardiovascular disease and Alzheimer's disease. The findings of this study are a significant extension of the coverage of CNVRs in the pig genome and provide valuable resources for follow‐up‐associated studies of CNVs in pig complex traits as well as important implications of human diseases.